Akupresur Menurunkan Tekanan Darah pada Pasien Hipertensi di Puskesmas Gang Kelor Kota Bogor - Agustina Agustina; Susmadi Susmadi; Ita Pursitasari; Eros siti Suryati; Franciscus Xaverius (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Hypertension remains a significant public health challenge in Indonesia, with a prevalence of 34.11% (approximately 90 million people). West Java Province reports one of the highest national prevalence rates at 39.60%, with 56,411 documented cases in Bogor City alone. Often termed